Effects of dietary glycerol, vitamin C and niacinamide supplementation on liver of growing-finishing pigs - Sun, Wenchen; Deng, Linglan; Zou, Wanjie; Wei, Panting; Hao, Shaobin; Wu, Huadong; Lu, Wei; He, Yuyong (Frontiers in Veterinary Science, 2025)
The influence of supplementing glycerol, vitamin C and niacinamide on the liver of growing-finishing pigs has not yet been examined. This study investigated the effect of 10% glycerol, 0.06% vitamin C and 0.05% niacinamide supplementation at single or combination on liver of growing-finishing pigs. Compared with pigs supplemented with 0% glycerol, 0% vitamin C and 0% niacinamide, pigs supplemented only with 10% glycerol had higher (p < 0.05) TNF-α concentration, partially hepatic steatosis, higher (p < 0.05) relative abundances of Escherichia_shigella, Prevotellaceae_UCG_003, Lachnospiraceae_XPB1014_group, Coprococcus, Lactococcus and Megamonas, lower (p < 0.05) solute carrier family 7 member 11 (SLC7A11) expression in liver tissue. However, pigs offered the diet with a mixture of 0.06% vitamin C and 0.05% niacinamide had higher (p < 0.05) relative abundance of Faecalibaculum and expression of SLC7A11, lower (p < 0.05) relative abundances of Staphylococcus and Clostridium_sensu_stricto_1 in liver tissue. Supplementation of 10% glycerol, 0.06% vitamin C and 0.05% niacinamide simultaneously to pigs increased (p < 0.05) the ferrous ion level, the relative abundances of Escherichia_Shigella, Lactococcus and Desulfobacterota, the expressions of gene Cryptochrome-1(CRY1) and SLC7A11, but decreased (p < 0.05) the expressions of gene C-reactive protein (CRP) and galactokinase 1 (GALK1) in liver tissue. Supplementation with 0.06% vitamin C and 0.05% niacinamide can alleviate the damage in liver of pigs fed a diet containing 10% glycerol.